Creating a Competency-Based Medical Education Curriculum for Canadian Diagnostic Radiology Residency (Queen's Fundamental Innovations in Residency Education)—Part 1: Transition to Discipline and Foundation of Discipline Stages. Issue 3 (August 2021) - Kwan, Benjamin Yin Ming; Mbanwi, Achire; Cofie, Nicholas; Rogoza, Christina; Islam, Omar; Chung, Andrew D.; Dalgarno, Nancy; Dagnone, Damon; Wang, Xi; Mussari, Ben
Purpose: The Royal College of Physicians and Surgeons of Canada (RCPSC) has mandated the transition of postgraduate medical training in Canada to a competency-based medical education (CBME) model divided into 4 stages of training. As part of the Queen's University Fundamental Innovations in Residency Education proposal, Queen's University in Canada is the first institution to transition all of its residency programs simultaneously to this model, including Diagnostic Radiology. The objective of this report is to describe the Queen's Diagnostic Radiology Residency Program's implementation of a CBME curriculum. Methods: At Queen's University, the novel curriculum was developed using the RCPSC's competency continuum and the CanMEDS framework to create radiology-specific entrustable professional activities (EPAs) and milestones. In addition, new committees and assessment strategies were established. As of July 2015, 3 cohorts of residents (n = 9) have been enrolled in this new curriculum. Results: EPAs, milestones, and methods of evaluation for the Transition to Discipline and Foundations of Discipline stages, as well as the opportunities and challenges associated with the implementation of a competency-based curriculum in a Diagnostic Radiology Residency Program, are described. Challenges include the increased frequency of resident assessments, establishing stage-specific learner expectations, and the creation of volumetric guidelines for case reporting and procedures. Conclusions: Development of a novel CBME curriculum requires significant resources and dedicated administrative time within an academic Radiology department. This article highlights challenges and provides guidance for this process.